Analisis Strategi Bisnis Pada IKM (Industri Kecil Menengah) Kerajian Tradisional Allysia Tapis Lampung Di Kelurahan Yosodadi-Metro Timur Di Tengah Persaingan Bisnis - Selamet Fuadi; Nina Lelawati; Regita Haryanti (Universitas Muhammadiyah Metro, 2025)
The Traditional Crafts Industry, especially the Small and Medium Enterprises (SMEs) ofAllysa Tapis Lampung, faces challenges in business competition and the sustainability oftheir business amidst dynamic changes in the business environment and diverse consumerpreferences. The main obstacles faced are increasingly fierce competition, limited access towide markets, ineffective marketing strategies, and constraints in product innovation. Thisstudy aims to analyze the business strategy in SMEs of Traditional Crafts Allysa TapisLampung in Yosodadi-Metro Timur Village in facing increasingly fierce businesscompetition. The research was conducted using a qualitative approach with a descriptivemethod. Data collection methods include interviews, observations, and documentation.Primary data were obtained directly from informants through interviews with the owners ofAllysa Tapis Lampung SMEs in Yosodadi Metro Timur. Meanwhile, secondary data wereobtained from various references related to the research. The results of the analysis indicate that Allysa Tapis Lampung SMEs face various challenges in maintaining theircompetitiveness in the market. Therefore, several business strategies are proposed, includingproduct diversification, quality improvement, market expansion, and branding reinforcement.Additionally, collaborative efforts with local governments and other relevant parties are alsoconsidered important to support the growth of these SMEs. In conclusion, it is found thatAllysa Tapis Lampung SMEs can enhance their competitiveness by utilizing digital marketingstrategies, adapting to changes in consumer trends, and conducting comprehensive analysesof changes in monthly income and influencing factors